Performance Comparison of Downlink Packet Scheduling Algorithms in LTE Network - Mohd. Algharem; Mohd. Hasbullah Omar; Muhammed I. Alghamdi; Rahmat Budiarto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Long Term Evolution (LTE) was introduced by the Third-Generation Partnership Project (3GPP) and is considered as the latest step towards the fourth generation of radio technology. This paper investigates the performance of well-known packet scheduling algorithms such as Proportion Fair (PF), Maximum- Largest Weighted Delay First (M-LWDF), Exponential Proportion Fair (EXP/PF), Frame Level Scheduler (FLS), Exponential rule (EXP rule), and Logarithmic rule (LOG Rule) in terms of delay, throughput, and packet loss ratio (PLR) by using the LTE-Sim open source simulator. Different traffic types are used, and Simulation results show that in video traffic, FLS and EXP algorithms provide a higher system throughput compared to other algorithms while keeping the delay and packet loss ratio small. However, in the case of best-effort traffic, results show a high delay and PLR with low throughput. The main contribution of this paper is to determine the appropriate downlink scheduling algorithm for VOIP, video, and best-effort traffics in 3GPP LTE.